Early Serum Heme Oxygenase-1, Soluble Vascular Endothelial Growth Factor Receptor-1, and B-Cell Lymphoma/Leukemia-2 Levels and Unfavorable Obstetric Outcomes - Sutcu, Havva; Varol, G. Fusun; Inan, Cihan; Uzun, Isil; Sayin, N.Cenk (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: To examine early pregnancy levels of serum heme oxygenase-1, soluble vascular endothelial growth factor receptor-1, B-cell lymphoma/leukemia-2 in relation to unfavorable pregnancy outcomes, including preeclampsia, fetal growth restriction, spontaneous preterm birth, gestational diabetes mellitus and fetal macrosomia. STUDY DESIGN: A total of randomly selected 140 pregnancies were included in this prospective study. Peripheral blood samples were obtained between 110/7 and 136/7 gestational weeks. All pregnancies were followed up until the outcomes were obtained and classified as preeclampsia, fetal growth restriction, spontaneous preterm birth, gestational diabetes mellitus, fetal macrosomia, and uncomplicated ones. RESULTS: Significantly high levels of early serum heme oxygenase-1 were found in the cases who subsequently developed preeclampsia, spontaneous preterm birth, and fetal macrosomia (p<0.05), in concordance with high soluble vascular endothelial growth factor receptor-1 levels of the preeclampsia group, however, B-cell lymphoma/leukemia-2 s were similar in all groups. As soluble vascular endothelial growth factor receptor-1 predicted preeclampsia at a value of 11.905 ng/mL, the cutoff values for the heme oxygenase-1 to predict preeclampsia, spontaneous preterm birth, and fetal macrosomia were 0.372 ng/mL, 0.354 ng/mL and 0.494 ng/ml, respectively. CONCLUSION: Elevated first trimester heme oxygenase-1 levels are remarkable in the pregnancies associated with preeclampsia, spontaneous preterm birth, and fetal macrosomia in comparison with uncomplicated ones.